Artemisinin modulating effect on human breast cancer cell lines with different sensitivity to cytostatics - Chekhun, V.F.; Lukianova, N.Y.; Borikun, T.V.; Zadvornyi, T.V.; Mokhir, A. (Experimental Oncology, 2017)
Aim: To explore effects of Artemisinin on a series of breast cancer cells with different sensitivity to typical cytotoxic drugs (doxorubicin — Dox; cisplatin — DDP) and to investigate possible artemisinin-induced modification of the mechanisms of drug resistance. Materials and Methods: The study was performed on wild-type breast cancer MCF-7 cell line (MCF-7/S) and its two sublines MCF-7/Dox and MCF-7/DDP resistant to Dox and DDP, respectively. The cells were treated with artemisinin and iron-containing magnetic fluid. The latter was added to modulate iron levels in the cells and explore its role in artemisinin-induced effects. The MTT assay was used to monitor cell viability, whereas changes of expression of selected proteins participating in regulation of cellular iron homeostasis were estimated using immunocytochemical methods. Finally, relative expression levels of miRNA-200b, -320a, and -34a were examined by using qRT-PCR. Results: Artemisinin affects mechanisms of the resistance of breast cancer cells towards both Dox and DDP at sub-toxic doses. The former drug induces changes of expression of iron-regulating proteins via different mechanisms, including epigenetic regulation. Particularly, the disturbances in ferritin heavy chain 1, lactoferrin, hepcidin (decrease) and ferroportin (increase) expression (р ≤ 0.05) were established. The most enhanced increase of miRNA expression under artemisinin influence were found for miRNA-200b in MCF-7/DDP cells (7.1 ± 0.98 fold change), miRNA-320a in MCF-7/Dox cells (2.9 ± 0.45 fold change) and miRNA-34a (1.7 ± 0.15 fold change) in MCF-7/S cells. It was observed that the sensitivity to artemisinin can be influenced by changing iron levels in cells. Conclusions: Artemisinin can modify iron metabolism of breast cancer cells by its cytotoxic effect, but also by inducing changes in expression of iron-regulating proteins and microRNAs (miRNAs), involved in their regulation. This modification affects the mechanisms that are implicated in drug-resistance, that makes artemisinin a perspective modulator of cell sensitivity towards chemotherapeutic agents in cancer treatment.